Lightup project: development of a concept for a non-profit organization - Frazão, Inês Cristina Narciso (2018)
The main objective of this study is to develop a strong and coherent concept, able to sustain the added value of lightUP project. Through the development of various analysis, from the general market to the organization itself, this project is intended to represent an added value (both for society, as well as for volunteers and partners). It is an aim of the author to give the maximum focus, commitment and strength during every stage of the thesis, making sure that this will be not just a final requirement of the master, but a beginning of a community transformation. This organization will be centered on people’s well being, not focusing on material support, but on the emotional support. Being the Portuguese one of the most pessimistic people of the Europe, it is an aim to contribute to the change of this reality, starting by adults, enhancing the positivism that exists on each individual and that can be replicated to others. There are other goals to be achieved, such as finding the right practices in order to make sure that: (1) The organization will create truly impact, besides being irreverent; (2) The role of the organization is notorious, easily identified by society; (3) Volunteers will be volunteers for life (being informal volunteers in their daily lives, after passing through the project); (4) The social impact will be measured regularly and will be as accurate as possible and (5) The financial sustainability will be treated efficiently.